Primary sclerosing cholangitis, autoimmune hepatitis, and overlap in utah children: Epidemiology and natural history. Issue 4 (13th August 2013) - Deneau, Mark; Jensen, M. Kyle; Holmen, John; Williams, Marc S.; Book, Linda S.; Guthery, Stephen L.
<x xml:space="preserve">Abstract</x> The epidemiology and natural history of pediatric primary sclerosing cholangitis (PSC), autoimmune sclerosing cholangitis (ASC), and autoimmune hepatitis (AIH) are not well characterized. Using multiple, overlapping search strategies followed by a detailed records review, we identified all cases of pediatric PSC, ASC, AIH, and inflammatory bowel disease (IBD) in a geographically isolated region of the United States. We identified 607 cases of IBD, 29 cases of PSC, 12 cases of ASC, and 44 cases of AIH. The mean age at diagnosis was 13.0 years for PSC, 11.3 years for ASC, and 9.8 years for AIH. The incidence and prevalence of PSC, ASC, and AIH were 0.2 and 1.5 cases, 0.1 and 0.6 cases, and 0.4 and 3.0 cases per 100, 000 children, respectively. The mean duration of follow‐up was 5.9 years. The probability of developing complicated liver disease within 5 years of the diagnosis of liver disease was 37% [95% confidence interval (CI) = 21%‐58%] for PSC, 25% (95% CI = 7%‐70%) for ASC, and 15% (95% CI = 7%‐33%) for AIH. The 5‐year survival rates with the native liver were 78% (95% CI = 54%‐91%) for PSC, 90% (95% CI = 47%‐99%) for ASC, and 87% (95% CI = 71%‐95%) for AIH. Cholangiocarcinoma developed in 2 of the 29 PSC patients (6.9%). PSC occurred in 9.9% of patients with ulcerative colitis (UC) and in 0.6% of patients with Crohn's disease (CD). ASC occurred in 2.3% of UC patients and 0.9% of CD patients. AIH occurred in 0.4% of UC patients and in 0.3% of CD patients. Liver disease occurred in 39 of 607 IBD patients (6.4%) overall. Conclusion: Immune‐mediated liver diseases are important sources of morbidity in children. Using a population‐based design, this study quantifies the burden and natural history of immune‐mediated liver disease in children. (Hepatology 2013;58:1392–1400)